Rheological properties of cassava starch-kaffir lime film solution - Mohamed Khalid, Nurul Jannah (2019)
Rheological properties of biodegradable film are very important because it effects the final properties of film solutions. Rheological behaviour of cassava starch-kaffir lime film solutions was studied with the shear rate range of 1-50 s-1 at different concentration (3.0, 3.5, 4.0, 4.5 and 5.0 wt.%) and temperature (30, 40, 50, 60 and 70℃) using a controlled stress rheometer. To describe the rheological behaviour of film solutions, a power law model equation was used while for the effect of temperature, Arrhenius equation was used to evaluate. To determine the effect of starch concentration on viscosity, the exponential model was used. From this study, it is shows that the flow behaviour index (n) value decrease with the increasing of concentration where film solutions with various concentration shows shear-thinning or pseudoplastics behaviour. For consistency index (K) value, it is shows increasing with concentration while decreased with the increasing of temperature. The amount of starch and temperature effect the activation energy (Ea) of film solutions. It can be concluded that concentration of starch and temperature had a huge and significant effect on the rheology properties of cassava starchkaffir lime film solutions.